ANALISIS KEPATUHAN WAJIB PAJAK BADAN DI INDONESIA: SEBUAH META ANALISIS - Anthony Erlangga Assan; Theresia Woro Damayanti (Jurnal Akuntansi, 2017)
The purpose of this research is to find  the new conclusion for the corporate tax  compliance. This research use the meta anaylisis approach. Meta-analysis approach is expected to give the new conclusion based on previous research in the corporate tax  compliance. The on previous research in the corporate tax  compliance has many conclusion, so this research used meta-analysis approach  to synthesize the factors that has significant influence on corporate tax  compliance. The research is using the published article as sample form 2004-2015. This research find that modernization of tax administration, sanctions, service quality, understanding of tax accounting and audit have significant influence in corporate tax  compliance.